Gold meets selenium: dual activation of selenium-containing propargyl alcohols towards the synthesis of 2H-chromenes and mechanistic insights - Lopes, Eric F.; Dietl, Martin C.; Ziegler, Benjamin; Rudolph, Matthias; Barcellos, Thiago; Oeser, Thomas; Lüdtke, Diogo S.; Hashmi, A. Stephen K. (Chemistry - a European journal, 2024)
Herein, we report the synthesis of seleno-substituted chromenes from selenoalkynes and phenols. In this cascade reaction, the applied gold catalyst not only functions as a π-acid, but also as a Lewis acid, enabling the propargylic substitution in the first step to connect the oxygen carbon bond. Under the optimal reaction condition a total of 26 chromenes were accessible by this modular access. During scale up experiments, the hydrolysis of the vinylselenium substructure to the corresponding chromenones was observed. By revisiting the electron-rich starting materials, four chromenones were produced following a one-pot reaction using a single gold catalyst. To better understand the interaction of gold and selenium, a series of nuclear magnetic resonance studies and high-resolution mass spectrometry studies were performed, which led to the proposal of a mechanism for this transformation.